Efficacy of Pneumococcal Nontypable Haemophilus influenzae Protein D Conjugate Vaccine (PHiD-CV) in Young Latin American Children: A Double-Blind Randomized Controlled Trial - Tregnaghi, Miguel W.; Sáez-Llorens, Xavier; López, Pio; Abate, Hector; Smith, Enrique; Pósleman, Adriana; Calvo, Arlene; Wong, Digna; Cortes-Barbosa, Carlos; Ceballos, Ana; Tregnaghi, Marcelo; Sierra, Alexandra; et al. (PLoS medicine, 2014)
The relationship between pneumococcal conjugate vaccine-induced antibody responses and protection against community-acquired pneumonia (CAP) and acute otitis media (AOM) is unclear. This study assessed the impact of the ten-valent pneumococcal nontypable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) on these end points. The primary objective was to demonstrate vaccine efficacy (VE) in a per-protocol analysis against likely bacterial CAP (B-CAP: radiologically confirmed CAP with alveolar consolidation/pleural effusion on chest X-ray, or non-alveolar infiltrates and C-reactive protein ≥ 40 µg/ml); other protocol-specified outcomes were also assessed. This phase III double-blind randomized controlled study was conducted between 28 June 2007 and 28 July 2011 in Argentine, Panamanian, and Colombian populations with good access to health care. Approximately 24,000 infants received PHiD-CV or hepatitis control vaccine (hepatitis B for primary vaccination, hepatitis A at booster) at 2, 4, 6, and 15-18 mo of age. Interim analysis of the primary end point was planned when 535 first B-CAP episodes, occurring ≥2 wk after dose 3, were identified in the per-protocol cohort. After a mean follow-up of 23 mo (PHiD-CV, n = 10,295; control, n = 10,201), per-protocol VE was 22.0% (95% CI: 7.7, 34.2; one-sided p = 0.002) against B-CAP (conclusive for primary objective) and 25.7% (95% CI: 8.4%, 39.6%) against World Health Organization-defined consolidated CAP. Intent-to-treat VE was 18.2% (95% CI: 5.5%, 29.1%) against B-CAP and 23.4% (95% CI: 8.8%, 35.7%) against consolidated CAP. End-of-study per-protocol analyses were performed after a mean follow-up of 28-30 mo for CAP and invasive pneumococcal disease (IPD) (PHiD-CV, n = 10,211; control, n = 10,140) and AOM (n = 3,010 and 2,979, respectively). Per-protocol VE was 16.1% (95% CI: -1.1%, 30.4%; one-sided p = 0.032) against clinically confirmed AOM, 67.1% (95% CI: 17.0%, 86.9%) against vaccine serotype clinically confirmed AOM, 100% (95% CI: 74.3%, 100%) against vaccine serotype IPD, and 65.0% (95% CI: 11.1%, 86.2%) against any IPD. Results were consistent between intent-to-treat and per-protocol analyses. Serious adverse events were reported for 21.5% (95% CI: 20.7%, 22.2%) and 22.6% (95% CI: 21.9%, 23.4%) of PHiD-CV and control recipients, respectively. There were 19 deaths (n = 11,798; 0.16%) in the PHiD-CV group and 26 deaths (n = 11,799; 0.22%) in the control group. A significant study limitation was the lower than expected number of captured AOM cases. Efficacy was demonstrated against a broad range of pneumococcal diseases commonly encountered in young children in clinical practice. www.ClinicalTrials.gov NCT00466947.